Aloe vera enhances the innate immune response of pacu (Piaractus mesopotamicus) after transport stress and combined heat killed Aeromonas hydrophila infection - Zanuzzo, Fábio S. [UNESP]; Sabioni, Rafael E. [UNESP]; Montoya, Luz Natalia F. [UNESP]; Favero, Gisele [UNESP]; Urbinati, Elisabeth C. [UNESP] (Elsevier, 2017)
In this study, pacu (Piaractus mesopotamicus) were fed with diets containing Aloe vera for 10 days prior to transport stress and infection with heat killed Aeromonas hydrophila. A. vera is popular around the world due to its medicinal properties, including immunostimulatory effects which was observed in this study. The results show that transport causes immunosuppression, an effect that was prevented by A. vera. Specifically, A. vera prevented reductions of both leukocyte respiratory burst and hemolytic activity of complement system caused by transport. Further, fish fed with A. vera also showed significantly higher leukocyte respiratory burst, serum lysozyme concentrations and activity of complement system 24 h after bacterial infection. Additionally, we observed that A. vera may modulate the innate response through activation of complement system during bacterial immune stimulation. In summary, A. vera extract enhanced innate immune parameters and consequently the ability of fish to cope with pathogens following transport stress. These findings show that A. vera has promise for use in aquaculture and add further evidence that medicinal herbs added to fish feed assist to prevent disease outbreaks.
Keywords: Immunostimulant; Innate immune response; Medicinal herbs; Piaractus mesopotamicus; Stress